PENINGKATAN TEKNOLOGI BUDIDAYA PERIKANAN (The improvement of fish culture technology) - M. Fatuchri Sukadi (Jurnal Iktiologi Indonesia, 2002)
In the future, fish supply from aquaculture should be encouraged since its production from capture fisheries nearly reached the level-off condition. Aquaculture is a source of national economic growth and should be developed in such a way so that socially accepted, environmentally sound and competitively advantaged. The condition of aquaculture in Indonesia (in year 2000) is presented in this paper. Independent and dependent factors which influenced feasible aquaculture, and also the levels of technologies of aquaculture based on feed input and environmental modification are also presented as a basic aquaculture technology increase. AbstrakDi masa depan, pasokan hasil perikanan diharapkan berasal dari budidaya lebih besar dibandingkan dari penangkapan. Dengan demikian, budidaya ikan merupakan salah satu sumber pertumbuhan ekonomi yang harus diwujudkan melalui sitem budidaya yang berdaya saing, berkelanjutan dan berkeadilan. Pengembangan budidaya dilakukan baik di perairan tawar, payau dan laut yang keragaannya di tahun 2000 dikemukakan dalam tulisan ini. Faktor-faktor yang mempengaruhi kelayakan budidaya ikan yang terdiri dari faktor independen dan dependen, serta tingkat penerapan teknologi budidaya berdasarkan input pakan dan modifikasi lingkungan dibahas agar dijadikan dasar dalam peningkatan teknologi budidaya perikanan.